Sex aggregation and species segregation cues in swarming mosquitoes: role of ground visual markers - Poda, Serge B. (Parasit Vectors, 2019)
BACKGROUND: Mating swarm segregation in closely related insect species may contribute to reproductive isolation. Visual markers are used for swarm formation; however, it is unknown whether they play a key role in swarm location, species segregation and sex aggregation. METHODS: Using two sympatric closely related species of the Anopheles gambiae complex, An. coluzzii and An. gambiae (s.s.), we investigated in both laboratory and semi-field conditions (i) whether males of the two species use visual markers (black cloths) to locate their swarm; and (ii) whether the presence/absence and size of the marker may differentially affect swarm characteristics. We also investigated whether conspecific virgin females use these markers to join male swarm sites. RESULTS: We showed that males of the two species used visual markers but in different ways: An. coluzzii swarm right above the marker whereas An. gambiae (s.s.) locate their swarm at a constant distance of 76.4 ± 0.6 cm from a 20 × 20 cm marker in the laboratory setup and at 206 ± 6 cm from a 60 × 60 cm marker in the semi-field setup. Although increased marker size recruited more mosquitoes and consequently increased the swarm size in the two species, An. coluzzii swarms flew higher and were stretched both vertically and horizontally, while An. gambiae (s.s.) swarms were only stretched horizontally. Virgin females displayed a swarm-like behavior with similar characteristics to their conspecific males. CONCLUSIONS: Our results provided experimental evidence that both An. coluzzii and An. gambiae (s.s.) males use ground visual markers to form and locate their swarm at species-specific locations. Moreover, the marker size differentially affected swarm characteristics in the two species. Our results also showed that virgin females displayed a swarm-like behavior. However, these “swarms” could be due to the absence of males in our experimental conditions. Nevertheless, the fact that females displayed these “swarms” with the same characteristics as their respective males provided evidence that visual markers are used by the two sexes to join mating spots. Altogether, this suggests that visual markers and the way species and sexes use them could be key cues in species segregation, swarm location and recognition. [Image: see text]